Examining the Criterion Validity and Diagnostic Specificity of Self-Report Measures of Narcissism and Mania. (January 2021) - Watson, David; Ellickson-Larew, Stephanie; Stanton, Kasey; Levin-Aspenson, Holly F.; Khoo, Shereen
We examined the validity of self-report measures of narcissism and mania by relating them to interview-based ratings of psychopathology. Narcissism scales were taken from the Narcissistic Personality Inventory (NPI), the Personality Diagnostic Questionnaire–4+, and the Short Dark Triad. Mania measures included the Altman Self-Rated Mania Scale (ASRM) and scales taken from the Hypomanic Personality Scale (HPS) and Expanded Version of the Inventory of Depression and Anxiety Symptoms. Our analyses addressed two key issues. The first issue was whether these scales demonstrated significant criterion validity (e.g., whether the HPS scales correlated significantly with interview ratings of mania). The second issue was whether they displayed specificity to their target constructs (e.g., whether the NPI scales correlated more strongly with ratings of narcissistic personality disorder than with other forms of psychopathology). All of the narcissism scales—including all three NPI subscales—correlated significantly with interview ratings of narcissistic personality disorder and showed considerable evidence of diagnostic specificity. Most of the mania scales also displayed good criterion validity and diagnostic specificity. However, two measures—the ASRM and the HPS Social Vitality subscale—had weak, nonsignificant associations with interview ratings of manic episodes; these findings raise concerns regarding their validity as specific indicators of mania.